Medijski imperijalizam u svijetu kao posljedica kulturnog imperijalizma / Global Imperialism in Media Imperialism as a result of the Cultural Imperialism - Sefo, Mustafa (Pregled: časopis za društvena pitanja / Periodical for social issues, 2017)
Media and media content are widely consumed every day by millions of people around the world. Every hour, minute and second, someone somewhere is consuming one of the branches of the media. The media inform, educate, entertain, spread and promote ideas, influence the audience both positively and negatively. The dependence of the media has taken cultural, educational, social, moral and religious aspects of the world. People of today want to be part of what is at the moment the trend in the world. Most people mimic the lifestyle of some celebrities and all that has been taken from then existing cultural values. Media and communication imperialism is directly related to the activities of the media domination of one state over another. Ownership structure, distribution or content of the media in such country are under the influence of pressure from the media interest in some other country or group that is completely out of touch even with that country.